Assessment of Anxiety Before Surgery In Cardiac Surgery Patients Who Have No History of Anxiety: Supporting Factors and Postoperative Morbidity - Wizano, Yose; Kurnia, Dedy (Green Publisher Indonesia, 2022)
Anxiety is a negative or threatening emotion that a person feels in general, in the long term (anxiety trait), or in certain situations that fluctuates over time (anxiety state). The research method used is a systematic review conducted by looking for articles related to the assessment of factors supporting anxiety before surgery in cardiac surgery patients who do not have a history of postoperative anxiety and morbidity through an electronic database search, namely ProQuest, and Google Scholar conducted in June – August 2022. RESULTS AND DISCUSSION: Patients with preoperative heart surgery have a moderate-high level of anxiety with many influencing risk factors. The extent to which each patient manifests his or her preoperative anxiety depends on many factors such as the patient's susceptibility to preoperative anxiety, age, gender, past experience with surgery, educational status, type and degree of proposed surgery, current health status, and socioeconomic status. . Patients with high postoperative pain have high morbidity and mortality, poor recovery, impaired wound healing, poor satisfaction, and longer hospital stays. Conclusion: Based on the results of the study in this systematic review, it was shown that patients undergoing cardiac surgery showed moderate to high levels of preoperative anxiety, with little medical information obtained, especially those related to surgery. Many factors influence the emergence of anxiety in preoperative cardiac patients, including fear of postoperative complications, lack of preoperative information to patients about surgical methods and procedures and the anesthesia they will undergo, not having strong social support, fear of death, fear of the unknown, the danger of doctor or nurse error, the need for blood transfusions, and the patient's comorbidities. Preoperative psychosocial factors are associated with poor short-term and long-term outcomes after cardiac surgery, so the detection and assessment of the patient's anxiety level before undergoing cardiac surgery should be carried